Investing in School Readiness : An Analysis of the Cost-Effectiveness of Early Childhood Education Pathways in Rural Indonesia - Nakajima, Nozomi; Hasan, Amer; Jung, Haeil; Brinkman, Sally; Pradhan, Menno; Kinnell, Angela (World Bank, Washington, DC, 2016)
This paper presents evidence on the cost-effectiveness of early childhood education pathways in rural Indonesia. It documents the existence of substantial differences in school readiness between 6 to 9 year old children. Using detailed enrollment histories, it unpacks whether and how early education experiences explain these gaps. The analysis considers not only the sequence of services children enroll in, but also the age at which they enroll and the duration for which they enroll. The differences in primary school test scores between a child who has no early education exposure and a child who completes a full sequence at the developmentally appropriate age are 0.42 standard deviations in language and 0.43 standard deviations in mathematics, roughly equivalent to an additional 0.9 to 1.2 years of primary schooling. The paper analyzes the cost-effectiveness of various early education pathways in Indonesia to show that providing access to both playgroups and kindergartens to young children at developmentally appropriate ages can optimize public investments in early childhood education. The paper subjects the analysis to a variety of robustness checks, and concludes that children enrolled in play-based early education programs (playgroups) at age 3 or 4, followed by the country's more academically structured programs (kindergartens) at age 5 or 6, are more likely to be ready for primary school than children who do not follow this sequence. Compulsory pre-primary education policy should consider incorporating both playgroups and kindergartens.